2023
DOI: 10.3390/biom13121771
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glutamine Synthetase (GS) and Glutamate Synthase (GOGAT) in the Improvement of Nitrogen Use Efficiency in Cereals

Stefania Fortunato,
Domenica Nigro,
Cecilia Lasorella
et al.

Abstract: Cereals are the most broadly produced crops and represent the primary source of food worldwide. Nitrogen (N) is a critical mineral nutrient for plant growth and high yield, and the quality of cereal crops greatly depends on a suitable N supply. In the last decades, a massive use of N fertilizers has been achieved in the desire to have high yields of cereal crops, leading to damaging effects for the environment, ecosystems, and human health. To ensure agricultural sustainability and the required food source, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 158 publications
0
5
0
Order By: Relevance
“…High NH 4 + concentrations could produce toxicity and inhibit the N assimilation process [40]. Many studies have shown that Fd-GOGAT is mainly expressed in photosynthetic tissues, while NADH-GOGAT is expressed in non-photosynthetic plastid tissues [41]. The transcription levels of six GOGAT genes in wheat roots, stems, leaves, flag leaves and seeds were tested; it was shown that TaGOGAT2s were mainly expressed in leaves, while TaGOGAT3s were highly expressed in roots (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…High NH 4 + concentrations could produce toxicity and inhibit the N assimilation process [40]. Many studies have shown that Fd-GOGAT is mainly expressed in photosynthetic tissues, while NADH-GOGAT is expressed in non-photosynthetic plastid tissues [41]. The transcription levels of six GOGAT genes in wheat roots, stems, leaves, flag leaves and seeds were tested; it was shown that TaGOGAT2s were mainly expressed in leaves, while TaGOGAT3s were highly expressed in roots (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Genes found in QTL regions involved in metabolic processes, cellular activities, and catalytic functions, and key regulators such as transcription factors and transporters can be regarded as candidate genes for many agronomic traits, including NUE or GPC (Singh et al 2021). Example by (Nigro et al 2020), identi ed key genes in the GS/glutamate synthase (GOGAT) cycle, critical for N uptake and GPC control, within the GPC QTL regions of durum wheat (Fortunato et al 2023). The grain protein content gene GPC-B1 was identi ed and further cloned from a genomic region carrying the most signi cant QTL for GPC derived from wild emmer wheat (WEW) (Triticum turgidum ssp.…”
Section: )mentioning
confidence: 99%
“…In higher plants, two types of GS are presented with distinct subcellular localization: cytosolic GS1 and chloroplastic GS2 ( Yin et al, 2022 ). GS1 plays a crucial role in the initial assimilation of NH 4 + or NO 3 − from the soil and also participates in nitrogen assimilation from processes releasing NH 4 + , such as amino acid transamination and protein degradation during senescence ( Thomsen et al, 2014 ; Krapp, 2015 ; Fortunato et al, 2023 ). Conversely, GS2 is predominantly responsible for assimilating NH 4 + generated during photorespiration in chloroplasts ( Daniel-Vedele & Chaillou, 2005 ; Masclaux-Daubresse et al, 2010 ; Rashid et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, GS2 is predominantly responsible for assimilating NH 4 + generated during photorespiration in chloroplasts ( Daniel-Vedele & Chaillou, 2005 ; Masclaux-Daubresse et al, 2010 ; Rashid et al, 2022 ). The expression of GS gene is intricately regulated by factors such as light exposure, nitrogen availability, and the plant’s developmental stage ( Fortunato et al, 2023 ; Larios et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%